Integrated farming system models for livelihood security and doubling the farmers’ income – A case study in Meghalaya - Behera, U K; Mohapatra, P P (Indian Farming, 2021)
Integrated farming system proved potential for doubling farmers’ income, livelihood security and higher resource use efficiency. Such an approach is climate resilient. There should be efforts by the line department, scientists, NGOs and policy makers to promote IFS in the region for the sustainable development of small and marginal farmers. The entire philosophy of integrated farming system revolves round better utilization of time, money, resources and family labourers of farm families. The farm family gets scope for gainful employment round the year, thereby ensuring good income and better standard of living. It is high time that the scientists, administrators and planners should think on such lines and provide adequate facilities and encouragement to the small and marginal farmers and rural youth to go ahead with the integrated farming systems with a sense of commitment for the rural development in totality.